Port and Maritime Transport Challenges in West and Central Africa - Pálsson, Gylfi; Harding, Alan; Raballand, Gaël (World Bank, Washington, DC, 2014)
This Working Paper presents the current trends in maritime transport and port sectors in West and Central Africa (WCA), and proposes several policy recommendations to improve maritime transport and port efficiency in order to enhance economic growth. West and Central African economies, which depend on maritime transport for an overwhelming proportion of their trade, rely on efficient maritime transport and port sectors to be competitive on world markets. This paper was prepared for the Sub-Saharan Africa Transport Policy Program (SSATP), in the overall context of the World Bank's efforts for trade facilitation in Sub- Saharan Africa2 as a follow-up to the 1997 Second Cotonou meeting of West and Central Africa (WCA) Ministers.